Analisis Kegagalan pada Komponen Work Roll Setelah Perlakuan Panas - Rifqi Al Hakim Al Hakim; Herry Oktadinata (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2023)
There has been a failure on the work roll components of the nodular cast iron type after the heat treatment, and the failure is in the form of cracks on the surface. In the heat treatment process, it can cover the whole or part of the component, and the consequence is that some elements will crack due to internal stress. This failure analysis research aims to find out the causes failure of work roll component. In this study, were carried out a visual inspection, non-destructive testing of dye penetrant and ultrasonic test, chemical composition test, fractography test microstructure test, and Rockwell C hardness test for the failed work roll components. The results showed that the component had high hardness and become brittle fracture. The content of 0,275% chromium can influence the high hardness of a carbide former. This amount exceeds 0,10% of the chromium composition of nodular cast iron, which makes carbides difficult to remove through heat treatment. Cracks in work roll components can also be affected by stress concentrations due to sudden changes in cross-sectional area during heat treatment triggered by porosity, inclusions, and acute angles.